Cellular Self-Digestion Unveiled: Autophagy's Impact on Cancer - Chowdhury, Ashiqur Rahman Khan; Naser, Iftekhar Bin (Community Based Medical Journal, 2024)
Autophagy is a strictly controlled process in which cells break down and recycle their own components by transporting them to lysosomes. Multiple studies have shown that autophagy has a diverse range of physiological and pathological functions in cells. Autophagy in cancer has contradictory functions, serving as both a suppressor and a driver of tumor growth. Specifically, it may exhibit several roles in relation to cancer treatment, either leading to cancer resistance or enhancing susceptibility to radiation and chemotherapy. Hence, autophagy has the potential to augment the efficacy of anticancer medications and radiation treatment. CBMJ 2024 January: vol. 13 no. 01 P: 107-118